Progress on Drug Therapy for Opioid-induced Constipation - Jiachun NI, Zengjin CAI, Qiong JIANG, Haibo LAN, Xiangdong YANG, Wenbin FAN (Zhongguo quanke yixue, 2022)
Opioid-induced constipation (OIC) is one of the common adverse reactions of opioids, which may affect the quality of life and follow-up treatment compliance of patients. With the rise of number of cancer patients worldwide and the increase in the use of opioids in chronic non-cancerous pain, the number of OIC patients will increase accordingly. Therefore, how to achieve effective analgesia and balance the occurrence of analgesia and OIC is one of the clinical problems that need to be resolved urgently. At present, the main therapeutic drugs for OIC mainly include oral laxatives and peripheral μ-opioid receptor antagonists, secretagogues, traditional Chinese medicines, etc. This paper mainly analyzed the drug therapy of OIC, in order to provide a reference for the effective clinical prevention and treatment of OIC.